2015
DOI: 10.11604/pamj.2015.22.26.7116
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for cervical cancer and pre-cancerous lesions in Rwanda

Abstract: IntroductionCervical cancer prevalence in Rwanda has not been well-described. Visual inspection with acetic acid or Lugol solution has been shown to be effective for cervical cancer screening in low resource settings. The aim of the study is to understand the prevalence and risk factors for cervical cancer and pre- cancerous lesions among Rwandan women between 30 and 50 old undergoing screening.MethodsThis cross-sectional analytical study was done in 3 districts of Rwanda from October 2010 to June 2013. Women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
82
1
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(110 citation statements)
references
References 15 publications
17
82
1
10
Order By: Relevance
“…This was a comparable finding with a study conducted in Rwanda that found multiple sexual partner is a risk factor for cervical cancer (COR = 1.40; 95% CI 0.85–2.30) [17]. This association of cervical cancer with sexual behavior also was shown in a case–control study done in Manchester, England where the number of sexual partners was the risk factor (OR for six or more = 3.89) [18].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This was a comparable finding with a study conducted in Rwanda that found multiple sexual partner is a risk factor for cervical cancer (COR = 1.40; 95% CI 0.85–2.30) [17]. This association of cervical cancer with sexual behavior also was shown in a case–control study done in Manchester, England where the number of sexual partners was the risk factor (OR for six or more = 3.89) [18].…”
Section: Discussionsupporting
confidence: 89%
“…The sample size of this unmatched case–control study was calculated by using Stat cal in epi-info 7 by the following assumptions. Level of confidence 95, 80% power, proportion of controls who begun sexual intercourse before the age of 20 year odds ratio of 60% for the development of precancerous lesions of the cervix [17], Odds ratio 3 and case to control ratio 1:2. This gives the total sample size of 164 individuals: 55 cases and 109 controls.…”
Section: Methodsmentioning
confidence: 99%
“…This is in contrast with developed regions such as Europe were much lower incidence rates (11.9 per 100,000) have been reported [27]. This difference with the developed world may be as a result of differences in the prevalence of risk factors for cervical cancer such as early age at first intercourse [28], total number of lifetime sexual partners, sexual practices [29], and early age at first pregnancy [28]. The widespread availability of population based screening programs for cervical cancer in developed countries has also contributed to reduced incidence while HIV infection in Africa is contributing to increased incidence [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…4 In another study done by Makuza et al on prevalence and risk factors of cervical cancer and precancerous lesion in Rwanda, the mean age was 37.0 years. 5 The high incidence of screening at 30-40 years of age may be due to knowledge regarding screening opportunities for carcinoma cervix at this age. In our study, parity 3 women 42.8% (n=195) were screened more than other parity.…”
Section: Discussionmentioning
confidence: 99%